Fibrillation mechanism of glucagon in the presence of phospholipid bilayers as revealed by 13C solid-state NMR spectroscopy. (March 2019) - Yamane, Izumi; Momose, Ayano; Fujita, Hideki; Yoshimoto, Eri; Kikuchi-Kinoshita, Akie; Kawamura, Izuru; Naito, Akira
Highlights: Glucagon forms fibril aggregates in the acetic acid solution in the absence and presence of bicelles. N- and C-terminal α-helices changed to β-sheets in the fibril formation of glucagon in the absence of bicelles. N-terminal α-helix remained α-helix in the fibril formation of glucagon in the presence of bicelle. Fibrillation process of glucagon can be explained by a two-step autocatalytic reaction mechanism. Fibril nucleation and elongation in the presence of bicelles are faster and slower than those in the absence of bicelles. Abstract: Glucagon is a 29 amino acid peptide hormone secreted by pancreatic α−cells and interacts with specific receptors located in various organs. Glucagon tends to form gel-like fibril aggregates that are cytotoxic because they activate apoptotic signaling pathways. To understand mechanism of fibril formation, we investigated the structure and kinetics of glucagon fibril formation using 13 C solid-state NMR spectroscopy. In aqueous acetic acid solution at pH 3.3, distorted α−helical structure appeared around Gly4, Leu14, Ala19 and Leu26 in the monomeric form. In contrast, Gly4 and Ala19 were involved in β-sheet structures in the fibril form. The fibrillation process can be explained by a two-step autocatalytic reaction mechanism in which the first step is a homogeneous nuclear formation (k1 ), and the second step is an autocatalytic heterogeneous fibrillation process (k2 ). The rate constants k1 and k2 were separately determined in the acetic acid solution. Fibril formation was further investigated in the presence of lipid bilayers to mimic the physiological condition. We used bicelles which form discoidal nano-particles as the bilayer system and observed that the N-terminal α-helix did not change to β-sheet when fibrils formed in the presence of bicelles. Rate constant k1 became faster and k2 became slower in the presence of bicelles compared to the case in the absence of bicelles. Our findings reveal that the structure and kinetics of fibril formation by glucagon are altered in the presence of lipid bilayers.